Stock, distribution, preservation and structure of organic matter in soils of a climo-biosequence from a pedogenic perspective - Haghighi, Amir Hossein Jafarzadeh (2016)
Soil organic matter (SOM) represents the largest terrestrial pool of carbon (C). SOM characteristics such as stock, vertical distribution, preservation, and structural composition have been scarcely explored from pedogenic perspective. This study focused on a climo-biosequence in the Main Range of Peninsular Malaysia since it presents an opportunity to study the impacts of soil-forming factors, pedogenic processes, and soil properties on SOM characteristics. Soil samples from all genetic horizons of four representative soil profiles were subjected to routine physical,chemical, and mineralogical analyses. Particle-size fractionation and fulvic acid and humic acid extraction in combination with solid-state 13C nuclear magnetic resonance spectroscopy, Fourier-transform infrared spectroscopy, and scanning electron microscopy were used as specific methods. Soil organic carbon stock to 1 m depth increased along the studied climo-biosequence, from 5.7 kg m-2 in Udult to 8.9 kg m-2 in Humult to 15.8 kg m-2 in Orthod, reaching a maximum value of 49.6 kg m-2 in Saprist. An increase in the proportion of fulvic acid with depth in soils where podzolization was the active pedogenic process showed the translocation of fulvic acid from the A-horizon toward the B-horizon. Close relationships between the content of organic carbon (OC) in the <53 μm fraction and indicators of Fe oxides and allophanetype aluminosilicates in the B-horizon indicated the importance of Fe oxides and poorly crystalline aluminosilicates for preservation of OC in the subsoil. Alkyl C (20.1-75.2%) and O-alkyl C (16.8-67.7%) dominated the bulk soils and particle-size fractions. The proportion of alkyl C in the bulk soils and particle-size fractions of Ahorizon increased with increasing levation, while O-alkyl C showed opposite trend. This study demonstrates that SOM characteristics such as stock, vertical distribution,preservation, and structural composition are controlled by soil-forming factors (i.e.climate and vegetation), pedogenic processes, soil properties (i.e. texture and mineralogy), and pedogenesis, respectively.